Types of Plagiarism Found in Student â€œSkripsiâ€ at English Education Department of Halu Oleo University - Hasanah, Chici Faradillah; Mursalim, Mursalim; Muhsin, Muh. Khusnun (Journal of Teaching of English, 2021)
This study aimed at analyzing the types of plagiarism found in students Skripsi at English Education Department of Halu Oleo University, and to know the common factors that make students commit plagiarism. This research used descriptive qualitative research design and employed content analysis method. The researcher used 3 soft copies Skripsi of 2018 and 2020 of the graduated students and the interview result as the data sources. The instruments of this study were a checklist types of plagiarism adopted from KP Nasional (2014) and an interview guideline. In collecting and analysing the data, the researcher used a checklist that consisted of 1 to 5 types and the researcher would be giving the codes for every element that fulfil the criteria from Kementerian (2010) by manual checking using the help of Quetext software, and also used interview guideline to gain the data needed about the factors that make students commit plagiarism in their Skripsi. The results of this research show that: there are some types of plagiarism found in students Skripsi through first types (citing terms, words, or sentence of data and information from source) with a frequency of 11 paragraphs in entire students Skripsi, and the second types (randomly quoting terms, words, sentences or information from source) with a frequency of 6 paragraphs in entire students Skripsi, and third types through (using sources of ideas, opinions, or theories from original sources) with frequency 18 paragraphs in entire student Skripsi 3. There are several factors that make students commit plagiarism including friendâ€™s relation, personal ability, technology support, and less understanding of knowledge from students. To conclude, it is clear that plagiarism of idea is the most dominant type of plagiarism found in students Skripsi at English Education Department of Halu Oleo University.